A novel tumor-promoting mechanism of IL6 and the therapeutic efficacy of tocilizumab: Hypoxia-induced IL6 is a potent autophagy initiator in glioblastoma via the p-STAT3-MIR155-3p-CREBRF pathway. Issue 7 (2nd July 2016) - Xue, Hao; Yuan, Guang; Guo, Xing; Liu, Qinglin; Zhang, Jinsen; Gao, Xiao; Guo, Xiaofan; Xu, Shugang; Li, Tong; Shao, Qianqian; Yan, Shaofeng; Li, Gang
ABSTRACT: Hypoxia induces protective autophagy in glioblastoma cells and new therapeutic avenues that target this process may improve the outcome for glioblastoma patients. Recent studies have suggested that the autophagic process is upregulated in glioblastomas in response to extensive hypoxia. Hypoxia also induces the upregulation of a specific set of proteins and microRNAs (miRNAs) in a variety of cell types. IL6 (interleukin 6), an inflammatory autocrine and paracrine cytokine that is overexpressed in glioblastoma, has been reported to be a biomarker for poor prognosis because of its tumor-promoting effects. Here, we describe a novel tumor-promoting mechanism of IL6, whereby hypoxia-induced IL6 acts as a potent initiator of autophagy in glioblastoma via the phosphorylated (p)-STAT3- MIR155-3p pathway. IL6 and p-STAT3 levels correlated with the abundance of autophagic cells and HIF1A levels in human glioma tissues and with the grade of human glioma, whereas inhibition of exogenous or endogenous IL6 repressed autophagy in glioblastoma cells in vitro. Knockdown of endogenous MIR155-3p inhibited IL6-induced autophagy, and enforced expression of MIR155-3p restored the anti-autophagic activity of IL6 inhibitors. We show that the hypoxia-IL6-p-STAT3- MIR155-3p -CREBRF-CREB3-ATG5 pathway plays a central role in malignant glioma progression, with blockade of the IL6 receptor by tocilizumab demonstrating a certain level of therapeutic efficacy in a xenograft model in vivo, especially in combination with temozolomide. Moreover, tocilizumab inhibits autophagy by promoting tumor apoptosis. Collectively, our findings provide new insight into the molecular mechanisms underlying hypoxia-induced glioma cell autophagy and point toward a possible efficacious adjuvant therapy for glioblastoma patients.